From Total Quality Control to Lean Six Sigma Evolution of the Most Important Management Systems for the Excellence - Chiarini, Andrea; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2012)
The main purpose of this paper is to compare and discuss the evolution of six important management systems: Japanese Total Quality Control (JTQC), Total Quality Management (TQM), Deming’s System of Profound Knowledge, Business Process Reengineering (BPR), Lean Thinking and Six Sigma. Indeed the contribution of this work lies in the concurrent analysis and classification, by the means of a literature review, of the results and critical implementation factors of the six systems. Deming’s Plan-Do-Check-Act (PDCA) has been used to classify the findings from the literature review.
1 Introduction -- 2 A historical path of the systems -- 3 Literature review concerning the comparison of the systems -- 4 Research methodology -- 5 Japanese Total Quality Control -- 6 Total Quality Management -- 7 Deming’s System of Profound Knowledge -- 8 Business Process Reengineering -- 9 Lean Thinking -- 10 Six Sigma -- 11 Discussion and comparison about the common characteristics of the systems -- 12 Lessons learned from the comparison and discussion -- 13 Conclusions -- 14 Agenda for future research.
Keywords: Production management; Operations Management